Model Kinerja Karyawan: Kompensasi dan Motivasi (Literature Review MSDM) - Juhaeroh Juhaeroh; Siti Oni Isnenti; Dian Wirtadipura (Prosiding Amal Insani Foundation, 2023)
Employees are one of the most critical elements in the company in achieving company goals. Employee performance is influenced by several factors that leaders need to know. A leader/manager must understand the strengths and weaknesses of each manager to maximize potential and minimize employee deficiencies. Factors that influence an employee's performance are motivation and compensation. Motivation is needed as an encouragement to be able to improve performance. Compensation can affect employee performance, while compensation can be in the form of money or other facilities. Compensation is given as a form of appreciation for the performance and responsibilities of employees at work.